Non-Disclosure of Sexual Orientation of Men Having Sex With Men (MSM): A Hidden Threat of HIV Transmission in Palembang, Indonesia (Jurnal Ilmu Kesehatan Masyarakat, 2023)
Men who engage in sexual relationships with other men (MSM) are consider a high-risk group for HIV transmission, with MSM in Indonesia accounting for 17.9% cases of HIV in 2020. This qualitative study aimed to understand better the factors determining MSMs' motivation to disclose their sexual orientation. This research employed a phenomenological approach to explore the disclosure experiences of MSM in Palembang City. In-depth interviews and observations were conducted with 11 purposively recruited MSM informants and five MSM outreach workers to ensure data triangulation. Documentation and observations of the participants were conducted during various activities at the Intan Maharani Foundation (IMF). MSM participants observed extreme caution when disclosing their sexual orientation and only chose to reveal their sexual orientation to a very limited network, such as close friends, who are  MSM, and at risk of HIV transmission. The hesitation to disclosing sexual orientation may be linked to the fact that only a few MSM had ever undergone an HIV test. MSMs, if they choose to, could share their status with Field Outreach (FO) during routine health check-ups. Findings of this study call for further research on barriers that hinder MSM from openly discussing their sexual orientation. Such research can inform policy and program developers on how to improve services, promote health literacy, foster confidence and trust among MSMs, hence facilitating their access to HIV services, enabling them to disclose their HIV status confidentially, safely, and in a respectful environment.